Cost Benefit Analysis of Mothership Concept and Investigation of Optimum Chartering Strategy for Offshore Wind Farms. (2015) - Dalgic, Yalcin; Lazakis, Iraklis; Dinwoodie, Iain; McMillan, David; Revie, Matthew; Majumder, Jayanta
Abstract: The focus of this research is the cost benefit analysis of the mothership concept and the investigation of the optimum chartering strategy, which brings financial and operational benefits. This is achieved by performing operational simulations in the offshore wind operational expenditure and logistics planning tool StrathOW-OM, which is developed by the University of Strathclyde and commercial partner organisations. In this paper, a fixed accommodation platform concept, two mothership concepts and different vessel chartering periods are simulated. The simulation results are compared with a base case scenario, in which the O&M activities are performed through a conventional onshore base. The simulation results show that significant travel time is spent in far offshore, if only a single conventional onshore base is utilised in the operations. Among different vessel chartering periods (continuous, only summer months, only winter months or combination of summer months and winter months), October-December is identified as the most critical period for chartering a mothership.